Burundi : Request for Debt Relief Under the Catastrophe Containment and Relief Trust-Press Release; Staff Report; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2020)
Economic impact. COVID-19 is having an adverse economic impact on Burundi. The pandemic is affecting Burundi through an evolving domestic outbreak and economic spillovers from the global and regional environment, including from the containment measures introduced in trading partners and neighboring countries. Economic growth projections for 2020 have been revised down by 5.3 percentage points to -3.2 percent in 2020. The pandemic has exacerbated pre-existing economic challenges and creates an external financing need of 4.7 percent of GDP in 2020 and 2021, mainly as a result of lower exports in line with lower foreign demand due to lower global growth and transportation bottlenecks from containment measures in other countries; elevated imports needs related in part to the planned fiscal spending aimed at responding to the pandemic; and reduced remittances inflows. The pandemic has also created a fiscal financing need of 6.9 percent of GDP, which will need to be met mainly from external sources.